1998
DOI: 10.1002/(sici)1099-0798(199823)16:4<393::aid-bsl317>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Police perspectives on responding to mentally ill people in crisis: perceptions of program effectiveness

Abstract: In this study, we sampled sworn police officers from three law enforcement agencies (n=452), each of which had different system responses to mentally ill people in crisis. One department relies on field assistance from a mobile mental health crisis team, a second has a team of officers specially trained in crisis intervention and management of mentally ill people in crisis, and a third has a team of in‐house social workers to assist in responding to calls. Calls involving mentally ill people in crisis appear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
198
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(217 citation statements)
references
References 17 publications
(10 reference statements)
7
198
0
10
Order By: Relevance
“…This could be, in part, due to a lack of cooperation between mental health systems and police. In a study of police perspectives on responding to mentally ill individuals in crisis, less than half of the officers reported that their mental health systems or emergency rooms were moderately or very helpful (Borum, Deane, Steadman & Morrissey, 1998). The lack of cooperation from emergency room staff may be a result of unavailability of resources to manage psychiatric patients.…”
Section: Background Literaturementioning
confidence: 99%
“…This could be, in part, due to a lack of cooperation between mental health systems and police. In a study of police perspectives on responding to mentally ill individuals in crisis, less than half of the officers reported that their mental health systems or emergency rooms were moderately or very helpful (Borum, Deane, Steadman & Morrissey, 1998). The lack of cooperation from emergency room staff may be a result of unavailability of resources to manage psychiatric patients.…”
Section: Background Literaturementioning
confidence: 99%
“…Research conducted in the USA has explored police officers' perspectives when responding to mentally disordered individuals in crisis (Borum, Deane, Steadman, & Morrisey 1998;Watson, Corrigan, & Ottati, 2004). Results indicate that whilst specialist officers trained in Crisis Intervention Teams (CIT) feel most prepared to deal with calls involving mental disorder, all police officers develop frames of reference or 'schemas' which guides how they may subsequently understand and respond to situations involving MD individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Noga et al (2016) has established that despite the mentally ill being in daily contact with the UK police, officers have underdeveloped links with mental health and social care services. Police officers are provided with little or no training in the identification and management of mental illness, making them highly dependent on the support of partner agencies (Adebowale, 2013;Borum, Deane, Steadman, Morrissey, & Williams Deane, 1998;Cummings & Jones, 2010;Mind & Victim Support, 2013). This has potentially significant consequences for the safety of both officers and vulnerable detainees (Adebowale, 2013;Krameddine, Demarco, Hassel, & Silverstone, 2013).…”
Section: Police and Mental Illnessmentioning
confidence: 99%